Model Desain Sistem Informasi Inventory Barang Pada Triopanca Mart - Dea Andini Andriati; Rani Laple Satria Putra (SAINTEKBU, 2021)
Triopanca mart is a mini-market belonging to the Infantry Battalion 305 Para Raider Unit located on Jl. Raya Teluk Jambe, Sirnabaya, Kec. Teluk Jambe Timur, Kab. Karawang, West Java 41360. This mini market operates in the retail sector, managed directly by members of the 305th Para Raider Infantry Battalion. The current running system, namely the data processing of incoming and outgoing goods, is still being recorded. Into a ledger according to receipts and stock inventory, only recorded on a piece of paper then copied back to the computer input using excel by the warehouse admin. Problems that often arise are usually related to the accuracy of the number of goods and stock information; sometimes, the information provided does not follow existing goods' availability. This study aims to create a web-based inventory information system model that can manage incoming and outgoing goods and inventory using the Waterfall method and the Unified Modeling Language (UML) for structural modeling.